Toward an Eco-Tafsir Paradigm: Integrating Qur'anic Cosmology, Environmental Ethics, and Sustainability in Quraish Shihab's Interpretation - Luthviyah Romziana; Intan Prasari (Universitas Darussalam Gontor, 2026)
This study contributes to strengthening ecological tafsir discourse and offers practical implications for education and environmental awareness based on Islamic values. The growing environmental crisis has prompted renewed interest in religious approaches to ecological sustainability. While previous studies have discussed Islamic environmental ethics, limited attention has been given to the ecological implications of Qur’anic cosmology in contemporary tafsir. This study investigates the ecological meaning of cosmological verses in the Qur’an through the interpretation of M. Quraish Shihab and examines their relevance to current environmental concerns. Using a qualitative library research design, data were collected from Tafsir Al-Mishbah and related academic literature, then analyzed through thematic and interpretive approaches. The study finds that Quraish Shihab’s interpretation emphasizes three interconnected ecological principles: mīzān (cosmic balance), khalīfah (human stewardship), and the prohibition of fasād (environmental destruction). These principles position humans as morally responsible agents in preserving ecological harmony. The analysis further shows that Qur’anic cosmology functions not only as a theological explanation of the universe but also as an ethical framework for environmental responsibility. The study demonstrates the relevance of ecological tafsir in addressing contemporary environmental challenges from an Islamic perspective.